Methodology for developing gamification-based learning programming language framework - Khaleel, Firas Layth; Ashaari, Noraidah Sahari; Wook, Tengku Siti Meriam Tengku; Ismail, Amirah (International Conference on Electrical Engineering and Informatics, 2017)
Students sometimes find it hard to learn new programming languages. They often confront unfamiliar programming terms that require the visualization of the processes that occur in the computer memory. Some researchers suggest that an enjoyable approach could be adapted even when learning difficult subjects. Studies have shown that applying Gamification elements in websites engage user's attention and thinking skills. Gamification refers to the use of game elements in a non-game context to increase engagement between humans and computers. There are various methodologies for educational game development, which combining instructional design with learning theories. The objective of this paper is to discuss a comprehensive methodology for developing and validating a Gamification-Based Programming Learning Framework. The framework are constructed by integrating learning theories, game elements and programming learning requirements. Both qualitative and quantitative research methods are employed. The methodology are divided into three phases namely, analysis, innovation and validation. Each phase consists of steps and evaluation which must be completed before moving to the next phase. This methodology could be adapted by other researchers to develop a learning-based or game-based learning framework.